Globalization, modernity, and the rise of religious fundamentalism : the challenge of religious resurgence against the end of history (Deus Ex Machina) /: the challenge of religious resurgence against the end of history (Deus Ex Machina). (2019) - Methenitis, Dimitrios
No abstract available